2008
DOI: 10.1002/jcb.21681
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of a HIF‐1α inhibitor, RX‐0047

Abstract: HIF-1α plays a major role in activating gene transcription and is important for maintaining homeostasis under hypoxic conditions. Since tumors are often in a hypoxic state, HIF-1α is a potential target for the development of novel cancer therapeutics. This study was performed to determine the antitumoral efficacy of an antisense HIF-1α inhibitor, RX-0047 on different human cancer cell lines (MDA-MB 231, HME50-T, PC-3, Panc-1 and A549) in vitro. A549 lung cancer and PC-3 prostate cancer cells containing a lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…In this context, our data further highlight the importance of histological NSCLC subtypes. As inhibitors of HIF-1 and CAIX have been developed and are under examination [54][55][56], we have shown that targeting the HIFs or their associated markers may yield diverging effects according to histological subtypes as a result of the different prognostic impacts of these markers. Increased knowledge about these hypoxia and metabolic markers in NSCLC tumor and stromal compartments will be vital in identifying different cancer cell phenotypes as candidates for specific molecular targeting.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, our data further highlight the importance of histological NSCLC subtypes. As inhibitors of HIF-1 and CAIX have been developed and are under examination [54][55][56], we have shown that targeting the HIFs or their associated markers may yield diverging effects according to histological subtypes as a result of the different prognostic impacts of these markers. Increased knowledge about these hypoxia and metabolic markers in NSCLC tumor and stromal compartments will be vital in identifying different cancer cell phenotypes as candidates for specific molecular targeting.…”
Section: Discussionmentioning
confidence: 97%
“…Liao et al (12) showed that lack of HIF-1␣ resulted in delayed tumor onset, reduced tumor growth, and a diminished number of blood vessels, leading to a later onset of lung metastasis of the spontaneous PymT-model. Other studies elucidated that HIF-1␣ depletion reduced the size of experimental bone metastases of a human breast carcinoma cell line in nude mice (13) and that inhibition of HIF-1␣ by a synthetic inhibitor blocked outgrowth of pulmonary metastases of a human lung carcinoma in an experimental xenograft metastasis assay (41). However, these studies could not resolve whether the antitumorigenic and antimetastatic effect of HIF-1␣ deficiency can only be attributed to decreased survival of tumor cells within unfavorable microenvironments or whether HIF-1␣ directly impacts on tumor cell invasiveness in vivo, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-responsive elements linked with luciferase reporter genes combined with optical imaging systems have been used for real-time observation of HIF-1 signal transduction activity in living subjects (36)(37)(38). However, these approaches are limited by depth penetration and the nature of tomography and cannot monitor the spatial heterogeneity of HIF-1 signal transduction activity.…”
Section: Discussionmentioning
confidence: 99%